Recurrent YAP1-TFE3 gene fusions in clear cell stromal tumor of the lung - Agaimy, Abbas; Stoehr, Robert; Michal, Michael; Christopoulos, Petros; Winter, Hauke; Zhang, Lei; Stenzinger, Albrecht; Michal, Michal; Mechtersheimer, Gunhild; Antonescu, Cristina R. (The American journal of surgical pathology, 2021)
Clear cell (hemangioblastoma-like) stromal tumor of the lung (CCST-L) is a recently described distinctive rare pulmonary neoplasm of unknown histogenesis and molecular pathogenesis. Only 7 cases have been reported in 2 recent studies, although additional cases might have been reported under the heading of extraneural pulmonary hemangioblastoma. We herein describe 4 CCST-L cases, 3 of them harboring a YAP1-TFE3 fusion. The fusion-positive tumors occurred in 3 women, aged 29, 56, and 69 years. All presented with solitary lung nodules measuring 2.3 to 9.5 cm. Histologically, all tumors showed similar features being composed of relatively uniform medium-sized epithelioid to ovoid cells with clear cytoplasm and small round monomorphic nuclei. Scattered larger cells with enlarged hyperchromatic nuclei and marked pleomorphism were noted in 2 cases. The tumors were associated with a hypervascularized stroma with variable but essentially subtle resemblance to capillary hemangioblastoma and perivascular epithelioid cell tumor (PEComa). Immunohistochemistry was negative for all lineage-specific markers. Targeted RNA sequencing showed a YAP1-TFE3 fusion in 3 of 4 cases. All 3 tumors showed homogeneous nuclear TFE3 immunoreactivity. Two patients were disease free at 36 and 12 months. The third patient had biopsy-proven synchronous renal and hepatic metastases, but extended follow-up is not available (recent case). The fourth case lacking the fusion affected a 66-year-old woman and showed subtle histologic differences from the fusion-positive cases, but had comparable TFE3 immunoreactivity. CCST-L represents a distinctive entity unrelated to hemangioblastoma and likely driven by recurrent YAP1-TFE3 fusions in most cases. The relationship of our cases to the recently reported “hemangioblastoma-like” CCST-L remains to be determined. Analysis of larger series is paramount to delineate the morphologic spectrum and biological behavior of this poorly characterized entity.